The Relationship Between Female Midwifery Students' Knowledge About Personal Hygiene And The Incidence Of Vaginal Discharge - Hariani, Afnisa; Sadya, Mutia (Benih : Journal of Midwifery, 2023)
Health is very important for all individuals. According to Republic of Indonesia Law No. 36 of 2009, health can be defined as a state of health both physically, mentally, spiritually and socially and economically. In order for individuals to be productive, they need to maintain their health, one of which is by paying attention to self-care or what is commonly known as personal hygiene. Personal hygiene is an action to maintain a person's cleanliness and health for well-being. General objective. To find out whether there is a relationship between the knowledge of midwifery students about personal hygiene and the incidence of vaginal discharge at the Madina Husada Midwifery Academy, Panyabungan District, Mandailing Natal Regency. To find out the relationship between the knowledge of midwifery students about personal hygiene and the incidence. Vaginal discharge at the Madina Husada Midwifery Academy, Panyabungan sub-district, Mandailing district, Christmas 2023 based on knowledge. To find out the relationship between female midwifery students' knowledge about personal hygiene. Types of research. Analytical research is research conducted on a group of research objects which aims to look at phenomena that occur in certain populations. This type of research is an analytical survey that relates the knowledge of midwifery students about personal hygiene to the incidence of vaginal discharge. Knowledge of midwifery students regarding personal hygiene and the incidence of vaginal discharge at the Madina Husada Panyabungan Midwifery Academy, Mandailing Natal Regency in 2023, the majority had sufficient knowledge, 34 people (50.0%). Midwifery students' knowledge about personal hygiene and the incidence of vaginal discharge at the Madina Husada Panyabungan Midwifery Academy, Mandailing Natal Regency in 2023, the majority had good knowledge, 14 people (23.5%) and the majority had poor knowledge, 18 people (26.5%)